“Will I be molded or crushed?” Artistic representations of student teachers’ identities and emotions - Kennedy, Laura M.; Glause, Kaitlin (Frontiers in Education, 2022)
This article reports on the findings from a cross-institutional study of how arts-based reflection helped teacher candidates to identify and express their thoughts, feelings, and actions regarding the process of learning to teach. Inspired by PostSecret (Warren, 2005), teacher candidates created anonymous artwork to represent their experiences as student teachers. Through their artwork, candidates highlighted moments of perceived dissonance between their teacher preparation program and K-12 school settings. Additionally, when selecting one piece of art as inspiration for a written reflection, teacher candidates gravitated toward the artwork that provided emotional windows and mirrors (Bishop, 1990; Style, 1988) into their own experiences. This study holds significance for recognizing and responding meaningfully to the difficult emotional work of learning to teach.